PERCEPTIONS OF AMBITIOUS BEHAVIOR PATTERNS IN STUDENT ACADEMIC COMPETITION - Geofakta Razali; Naurissa Biasini (Global Synthesis in Education Journal, 2023)
Perception is the process through which we assess others, focusing on the aspects of human behavior we choose to observe. This study delves into the perception of students' ambitious attitudes, an area still shrouded in debate over whether such ambition is beneficial or detrimental within student circles. We conduct a comprehensive analysis of this topic through literature reviews and support it with social judgment theory, which explores the "ego involvement" in an individual's interactions with others. This overarching view guides our examination of a common yet potentially significant psychological phenomenon among students. Sociopsychology, a branch of communication theory grounded in psychological (behavioral) evaluation, provides insight into the psychological orientation of information assessment. This approach in sociopsychological communication studies helps us understand why individuals act as they do, not just through their words but also through non-verbal actions such as tone of voice, body movement, and facial expressions.